Beyond Waiting Rooms: Exploring the Role of Administrative Processes and Staffing Levels in Outpatient Service Efficiency at a Dental and Oral Hospital in Padang, Indonesia - Rahmasari, Suci; Rahmi Khairani Aulia; Yona Ladyventini (HM Publisher, 2024)
Lengthy patient waiting times negatively impact patient satisfaction and overall healthcare service quality. This study investigates the influence of administrative processes and staffing levels on outpatient service efficiency at a dental and oral hospital in Padang, Indonesia. A mixed-methods approach was employed, incorporating quantitative data analysis of patient waiting times and qualitative exploration of administrative workflows and staff perspectives through interviews and observations. Simulated data was generated based on existing literature to supplement the analysis where specific data points were unavailable. Inefficient administrative processes, including manual patient registration and record-keeping, were identified as major contributors to extended waiting times. Inadequate staffing levels, particularly during peak hours, further exacerbated the issue. Qualitative findings revealed staff perceptions of workload burden and the need for streamlined workflows. The study underscores the critical role of administrative processes and staffing levels in outpatient service efficiency. Recommendations include the implementation of electronic health record systems, process re-engineering, and strategic staffing adjustments to enhance patient flow and overall service quality.